Pulmonary Disease Prevention Program Assistance Through Improving Residential Sanitation in the Working Area of the Pegirian Community Health Center, Surabaya in 2020 - Rachmaniyah Rachmaniyah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The risk of transmitting pulmonary tuberculosis in the family needs to be a concern, especially for toddlers and the elderly who have a lower immune system—as well as for people with HIV who have damaged the body's immune system. In preventing the transmission of pulmonary tuberculosis, the role of the family is very important, because one of the duties of the family is to provide care for family members who are sick and to prevent transmission to healthy family members through measures that must be implemented in their daily lives. Efforts to prevent disease transmission, especially TB, which can be done are to improve the conditions of houses and sanitation facilities to support the realization of a healthy house. A healthy house is a house with physical facilities that meet the requirements for the health of its occupants, such as the fulfillment of ventilation, lighting, humidity, and occupancy density; all of which must meet health requirements so that it does not become a medium for disease transmission. This community service activity aims to create healthy settlements to prevent the transmission of pulmonary TB disease in the working area of the Pegirian Community Health Center, Surabaya in 2020. The target of this activity was specifically aimed at people with pulmonary tuberculosis in the working area of the Pegirian Community Health Center, Surabaya. The approach was carried out by the methods of observation, interviews, counseling, demonstrations of proper handwashing, and motivating residents to create a healthy house and environment by giving assistance in the form of glass tiles and handwashing with soap souvenirs.